1995
DOI: 10.1074/jbc.270.11.5702
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Smooth Muscle Cell-derived, Gla-containing Growth-potentiating Factor for Ca2+-mobilizing Growth Factors

Abstract: Proliferation of vascular smooth muscle cells (VSMC) is triggered by two types of growth factors. One activates tyrosine kinase-type receptors and the other activates G-protein-coupled receptors. We found that a conditioned medium of rat VSMC contained a growth-potentiating activity for the latter type of growth factor, and we purified a 70-kDa growth-potentiating factor (GPF) from the conditioned medium. Analyses of GPF and its cDNA revealed GPF to be a gamma-carboxyglutamic acid-containing protein encoded by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
176
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(181 citation statements)
references
References 17 publications
4
176
1
Order By: Relevance
“…More recent studies have shown that Gas6 can similarly bind and activate Rse/Sky and Mer RTK, although with lower a nity (Chen et al, 1997;Mark et al, 1996;Nagata et al, 1996;Ohashi et al, 1995). Gas6 was shown to act as a growth factor for ®broblasts, Schwann cells, chondrocytes, thyroid and vascular smooth muscle cells (Goruppi et al, 1996;Li et al, 1996;Loeser et al, 1997;Nakano et al, 1995;Tanaka et al, 1998). In most of the cellular systems Gas6 has been reported to protect cells from apoptosis independently of its growth stimulating activity (Avanzi et al, 1997;Bellosta et al, 1997;Goruppi et al, 1996;, therefore suggesting that induction of proliferation and prevention of apoptosis could involve elements in distinct (parallel) pathways.…”
Section: Introductionmentioning
confidence: 99%
“…More recent studies have shown that Gas6 can similarly bind and activate Rse/Sky and Mer RTK, although with lower a nity (Chen et al, 1997;Mark et al, 1996;Nagata et al, 1996;Ohashi et al, 1995). Gas6 was shown to act as a growth factor for ®broblasts, Schwann cells, chondrocytes, thyroid and vascular smooth muscle cells (Goruppi et al, 1996;Li et al, 1996;Loeser et al, 1997;Nakano et al, 1995;Tanaka et al, 1998). In most of the cellular systems Gas6 has been reported to protect cells from apoptosis independently of its growth stimulating activity (Avanzi et al, 1997;Bellosta et al, 1997;Goruppi et al, 1996;, therefore suggesting that induction of proliferation and prevention of apoptosis could involve elements in distinct (parallel) pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, however, the Axl ligand, GAS-6, is only a weak mitogen in a restricted range of tissue such as 3T3, Schwann, and vascular smooth muscle cells (Goruppi et al, 1996;Gasic et al, 1992;Li et al, 1996) and appears to play a greater role in modulating cellular responses to other factors such as thrombin and angiotensin II (Nakano et al, 1995). That a ligand shows little mitogenic activity when interacting with a RTK with transforming function has been seen in the Eph receptor tyrosine kinase family (Brambilla et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The pleotropic effects of Gas6-Axl interactions in different tissues may be summarized as follows. In vascular smooth muscle, Gas6 was initially purified as a mediator of vascular smooth muscle proliferation (34). Later studies showed Axl upregulation at sites of vascular injury, suggesting a role for this receptor in vascular remodeling (29).…”
mentioning
confidence: 99%